Small Nucleolar Noncoding RNA SNORA23, Up-Regulated in Human Pancreatic Ductal Adenocarcinoma, Regulates Expression of Spectrin Repeat-Containing Nuclear Envelope 2 to Promote Growth and Metastasis of Xenograft Tumors in Mice - Cui, Lin; Nakano, Kenji; Obchoei, Sumalee; Setoguchi, Kiyoko; Matsumoto, Masaki; Yamamoto, Tsuyoshi; Obika, Satoshi; Shimada, Kazuaki; Hiraoka, Nobuyoshi (Gastroenterology (New York, N.Y. 1943), 2017)
Small nucleolar noncoding RNAs (snoRNAs) regulate function of ribosomes, and specific snoRNAs are dysregulated in some cancer cells. We investigated dysregulation of snoRNAs in pancreatic ductal adenocarcinoma (PDAC) cells. We investigated snoRNA expression in PDAC cell lines by complementary DNA microarray and quantitative reverse transcription polymerase chain reaction. In PDAC (n = 133), intraductal papillary mucinous neoplasm (n = 16), mucinous cystic neoplasm-associated PDAC (n = 1), and non-tumor pancreas (n = 8) and liver (n = 3) tissues from subjects who underwent surgical resection, levels of snoRNA were measured by quantitative reverse transcription polymerase chain reaction and compared with clinicopathologic parameters and survival times determined by Kaplan-Meier analysis. To examine snoRNA function, PDAC cells were transfected with snoRNA-antisense oligonucleotides flanked with amido-bridged nucleic acids, or snoRNA-expression plasmids, and analyzed in proliferation, colony formation, spheroid formation, and invasion assays. To identify snoRNA-related factors, cells were analyzed by gene expression and proteomic profiling and immunoblot assays. Mice were given intrasplenic injections of MIA PaCa2- or Suit2-HLMC cells; tumor-bearing nude mice were then given 3 weekly injections of an antisense oligonucleotides against SNORA23, a H/ACA-box type snoRNA, and tumor growth and metastasis to liver, blood, and pancreas were analyzed. Levels of SNORA23 increased and accumulated at the nucleolus in highly metastatic MIA PaCa2- or Suit2-HLMC cells compared with their parental cells. We detected SNORA23 in human PDAC specimens but not in non-tumor pancreatic tissue. PDAC level of SNORA23 correlated with invasion grade and correlated inversely with disease-free survival time of patients. Expression of SNORA23 in PDAC cells increased their invasive activity and colony formation, and spheroid formation was inhibited by SNORA23 knockdown. In gene expression and proteomic profile analyses, we found SNORA23 to increase expression of spectrin repeat-containing nuclear envelope 2 (SYNE2) messenger RNA and protein. Knockdown of SYNE2 in PDAC cells reduced their invasive activities and anchor-independent survival. Administration of SNORA23 antisense oligonucleotides to mice slowed growth of xenograft tumors, tumor expression of SYNE2, tumor cell dissemination, and metastasis to liver. We found expression of the snoRNA SNORA23, which mediates sequence-specific pseudouridylation of ribosomal RNAs, to be increased in human PDAC tissues compared with non-tumor tissues, and levels to correlate with tumor invasion grade and patient survival time. SNORA23 increases expression of SYNE2, possibly through modulation of ribosome biogenesis, to promote PDAC cell survival and invasion, and growth and metastasis of xenograft tumors in mice.